Mouthwash Formulation Co-Delivering Quercetin and Mint Oil in Liposomes Improved with Glycol and Ethanol and Tailored for Protecting and Tackling Oral Cavity - Ines Castangia; Maria Manconi; Mohamad Allaw; Matteo Perra; Germano Orrù; Sara Fais; Alessandra Scano; Elvira Escribano-Ferrer; Mansureh Ghavam; Maryam Rezvani; Maria Letizia Manca (MDPI AG, 2022)
The aim of this work was the simultaneous loading of quercetin and mint essential oil (mint oil) in phospholipid vesicles specifically tailored to obtain an antibacterial and antioxidant mouthwash. The vesicles were prepared using soy lecithin and Tween 80 as bilayer components, and a mixture of phosphate buffer solution (33%), propylene glycol (33%) and ethanol (33%) as dispersing phase. The formation of regularly shaped, spherical and unilamellar vesicles was confirmed by cryogenic transmission electron microscopy analyses. Similarly, light scattering results disclosed that the size of the vesicles increased by increasing the concentration of mint oil, but at the same time the high amount of mint oil ensured high stability, as the size of these vesicles remained unchanged during 12 months of storage. All tested formulations were highly biocompatible towards epithelial cells and capable of counteracting oxidative cell damages caused by hydrogen peroxide. Moreover, the vesicles prepared with the highest concentration of mint oil inhibited the proliferation of the cariogenic Streptococcus mutans (S. mutans) and Lactobacillus acidophilus (L. acidophilus).